Increasing the Brightness of Cyanine Fluorophores for Single‐Molecule and Superresolution Imaging. Issue 4 (2nd December 2013) - Klehs, Kathrin; Spahn, Christoph; Endesfelder, Ulrike; Lee, Steven F.; Fürstenberg, Alexandre; Heilemann, Mike
Abstract In spite of their relatively low fluorescence quantum yield, cyanine dyes such as Cy3, Cy5, or Cy7 are widely used in single‐molecule fluorescence applications due to their high extinction coefficients and excellent photon yields. We show that the fluorescence quantum yield and lifetime of red‐emitting cyanine dyes can be substantially increased in heavy water (D2O) compared with water (H2O). We find that the magnitude of the quantum yield increase in D2O scales with the emission wavelength, reaching a particularly high value of 2.6‐fold for the most red‐emitting dye investigated, Cy7. We further demonstrate a higher photon yield in single‐molecule superresolution experiments in D2O compared to H2O, which leads to an improved localization precision and hence better spatial resolution. This finding is especially beneficial for biological applications of fluorescence microscopy, which are typically carried out in aqueous media and which greatly profit from the red spectral range due to reduced cellular auto‐fluorescence.